Plasmonic Switching of the Reaction Pathway: Visible‐Light Irradiation Varies the Reactant Concentration at the Solid–Solution Interface of a Gold–Cobalt Catalyst. Issue 35 (18th June 2019) - Peiris, Erandi; Sarina, Sarina; Waclawik, Eric R.; Ayoko, Godwin A.; Han, Pengfei; Jia, Jianfeng; Zhu, Huai‐Yong
Abstract: Product selectivity of alkyne hydroamination over catalytic Au2 Co alloy nanoparticles (NPs) can be made switchable by a light‐on/light‐off process, yielding imine (cross‐coupling product of aniline and alkyne) under visible‐light irradiation, but 1, 4‐diphenylbutadiyne in the dark. The low‐flux light irradiation concentrates aniline on the catalyst, accelerating the catalytic cross‐coupling by several orders of magnitude even at a very low overall aniline concentrations (1.0×10 −3 mol L −1 ). A tentative mechanism is that Au2 Co NPs absorb light, generating an intense fringing electromagnetic field and hot electrons. The sharp field‐gradient (plasmonic optical force) can selectively enhance adsorption of light‐polarizable aniline molecules on the catalyst. The light irradiation thereby alters the aniline/alkyne ratio at the NPs surface, switching product selectivity. This represents a new paradigm to modify a catalysis process by light. Abstract : Flicking the switch : The product selectivity of two competing reactions—alkyne hydroamination and alkyne–alkyne homo‐coupling—occuring on catalyst Au2 Co alloy nanoparticles can be switched by visible‐light irradiation. Light irradiation concentrates aniline on the catalyst, accelerating the catalytic cross‐coupling by several orders of magnitude, while in the dark, homo‐coupling of two alkyne molecules is preferred.